2014
DOI: 10.1007/s00521-014-1646-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prediction of traffic flow using a binary neural network

Abstract: This paper introduces a binary neural network-based prediction algorithm incorporating both spatial and temporal characteristics into the prediction process. The algorithm is used to predict short-term traffic flow by combining information from multiple traffic sensors (spatial lag) and time-series prediction (temporal lag). It extends previously developed Advanced Uncertain Reasoning Architecture (AURA) k-nearest neighbour (k-NN) techniques. Our task was to produce a fast and accurate traffic flow predictor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…For traffic information forecasting methods, several studies used data mining techniques (e.g., linear regression [26,27], logistic regression (LR) [28], Bayesian classifier [29,30], k-nearest neighbors (kNN) [31][32][33], artificial neural network (ANN) [34][35][36][37], etc.) to analyze the historical traffic information and obtain the forecasted traffic information.…”
Section: Traffic Information Forecasting Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For traffic information forecasting methods, several studies used data mining techniques (e.g., linear regression [26,27], logistic regression (LR) [28], Bayesian classifier [29,30], k-nearest neighbors (kNN) [31][32][33], artificial neural network (ANN) [34][35][36][37], etc.) to analyze the historical traffic information and obtain the forecasted traffic information.…”
Section: Traffic Information Forecasting Methodsmentioning
confidence: 99%
“…For traffic information forecasting methods based on ANN, some studies proposed and applied ANN to forecast short-term traffic information, and the experimental results showed that the accuracy of using ANN was better than using other approaches [35][36][37]. Although a previous study classified road segments into several road types for reducing ANN models [35], the diverse traffic characteristics of road segments may exist in the same type of road.…”
Section: Traffic Information Forecasting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng and Su 22 developed a k-NN-LSPC (k-NN-linearly sewing principle component) for prediction of traffic volume, which outperformed eight other algorithms. Hodge et al 23 addressed the problem of short-term prediction of traffic flow through a scalable neural network-based k-NN predictor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus verifies the favorable estimated performance of neural network. Reference [7] utilized binary neural network to predict traffic flow and reached the effect of "training once, repeatedly use". But the BPNN remains to be improved on account of mainly three weaknesses.…”
Section: Introductionmentioning
confidence: 99%